Sistem Proteksi Sambaran Petir Kandang Ternak Koperasi Yufeed Berkah Mulia di Desa Rukti Endah Kecamatan Seputih Mataram Lampung Tengah - H Sinaga, Herman; Permata, Diah; Purwasih, Nining; R Harahap, Charles (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Indonesia’s geographical position along the equator results in high annual rainfall, which in turn contributes to a significant frequency of lightning strikes. One affected area is Rukti Endah Village, located in the Seputih Mataram District of Central Lampung, which records a high incidence of lightning activity—up to 24 strikes in January alone and more than 100 thunderstorm days annually. Consequently, implementing effective lightning protection measures is essential to safeguard human life, buildings, and livestock housed in livestock pen. This community service initiative aims to assess the requirements for and implement a lightning protection system that adheres to established standards for livestock facilities in Rukti Endah Village. These facilities are jointly managed by the local community through the Koperasi Yufeed Berkah Mulia. The scope of activities includes designing a comprehensive lightning protection system based on IEC 62305 standards. The design comprises three main components: a lightning rod system, a low-voltage electrical protection system, and a grounding system. The lightning rod system features a 50 cm-long conductive electrode installed on the rooftop and connected to the grounding system using a 16 mm² grounding cable. The low-voltage protection system utilizes Surge Protective Devices (SPDs) rated for 220 volts, also connected to the grounding system with a 16 mm² conductor. The grounding system will employ a single-rod method, with one grounding rod installed adjacent to the livestock enclosure. This program will be implemented by a team of four lecturers, supported by six students, with the goal of enhancing safety and resilience against lightning-related hazards in the community.